Routine Postoperative Admission to the Intensive Care Unit Following Repair of Nonsyndromic Craniosynostosis: Is it Necessary?. Issue 6 (September 2019) - Chocron, Yehuda; Azzi, Alain; Galli, Rafael; Alnaif, Nayif; Atkinson, Jeffrey; Dudley, Roy; Farmer, Jean-Pierre; Gilardino, Mirko S.
Abstract : Background: Cranial vault surgery for craniosynostosis is generally managed postoperatively in the intensive care unit (ICU). The purpose of the present study was to examine our center's experience with the postoperative management of otherwise healthy patients with nonsyndromic craniosynostosis (NSC) without routine ICU admission. Methods: A retrospective cohort study of patients with NSC operated using a variety of vault reshaping techniques in our pediatric center between 2009 and 2017 was carried out. Patients with documented preexisting comorbidities that would have required admission to the ICU regardless of the surgical intervention were excluded. Results: A total of 102 patients were included in the study. Postoperatively, 100 patients (98%) were admitted as planned to a general surgical ward following observation in the recovery room. Two patients (2%) required ICU admission due to adverse intraoperative events. There were no patients who required transfer to the ICU from the recovery area or surgical ward. Within the surgical ward cohort, 6 patients (6%) had minor postoperative complications that were readily managed on the surgical floor. Postoperative anemia requiring transfusion was the most common complication. Conclusion: The results from this study suggest that otherwise healthy patients with NSC undergoing cranial vault surgery can potentially be safely managed without routine admission to the ICU postoperatively. Key elements are proper preoperative screening, access to ICU should an adverse intraoperative event occur and necessary postoperative surgical care. The authors hope that this experience will encourage other craniofacial surgeons to reconsider the dogma of routine ICU admission for this patient population. Abstract : Supplemental Digital Content is available in the text